Prevalence and risk factors for allergic rhinitis in bakers in Douala, Cameroon - Mbatchou Ngahane, Bertrand Hugo (BMJ Publishing Group, 2014)
OBJECTIVE: To determine the prevalence and risk factors of allergic rhinitis among bakers in Douala. DESIGN: A cross-sectional study; the logistic regression model was use to find the risk factors of allergic rhinitis. SETTING: The study was conducted in 42 bakeries randomly selected among a total of 151 bakeries in the city of Douala. PARTICIPANTS: All bakers who consented to participate in the study between 1 May and 31 July 2013. OUTCOME MEASURES: Allergic rhinitis was the outcome of interest. It was defined as the presence of the following symptoms: itchy nose, rhinorrhea, nasal obstruction and sneezing. RESULTS: During the study period, a total of 273 bakers were invited and 229 finally agreed to participate in this study. Males were the most represented gender with 222 (96.9%) participants. The mean age of the participants was 36.29±8.9 years. Smoking was found in 55 participants (24.5%). The symptoms of allergic rhinitis were observed in 24.5% of participants. Work related nasal symptoms were present in 15% of participants. Sensitisation to wheat flour and α-amylase was found in 16.6% and 8.3% of participants, respectively. The Prick test was positive for mites in 12.2% of participants. After multivariate analysis, sensitisation to flour (OR 3.95, 95% CI 1.85 to 8.47) and storage mites (OR 3.44, 95% CI 1.45 to 8.18) were the factors independently associated with symptoms of allergic rhinitis. CONCLUSIONS: Allergic rhinitis is frequent among bakers in Cameroon. Implementation of preventive measures against inhalation of airborne allergens in bakeries and clinical monitoring of bakers sensitised to wheat flour and mites could help to reduce the prevalence of allergic rhinitis among bakers.